Transatlantic Relations Among Radical Republican Circles During the Age of Revolutions - Emeryk Kuba (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
The constant flow of people, as well as goods and ideas in this oceanic environment, caused that in the second half of the 18th century the English and American republican circles strengthened their ties, with some women as notable activists. The English writer Catharine Macaulay (1731-1791), in addition to writing about the crucial events of the moment, crossed the ocean with the desire to be close and experience them in the first person. On the other hand, due to common interests, she maintained an intense epistolary relationship for more than twenty years with the American writer Mercy Otis Warren (1728-1814). Despite the limitations that they found in primarily male areas, such as history and politics, the contribution of these women was not limited to the expected support, but their concerns were reflected in some important writings for the Republican cause. Despite this and paradoxically, these revolutionary movements did not bring about significant changes in the situation and the rights of women.